Systematic review of the use and challenges of electronic health records in physiotherapy practice - André Moreira-Rosário; Carla Pereira; Sara Vaz; Carlos Rodrigues (BMJ Open, 2025)
Objective To synthesise current evidence on physiotherapists’ use of electronic health records (EHRs), with a focus on the determinants of adoption, implementation processes and associated implementation outcomes.Design A systematic review employing a narrative synthesis approach.Data sources PubMed, Cochrane, Scopus and Web of Science, covering all records from the inception of each database to 10 May 2024.Eligibility criteria Studies conducted in physiotherapy clinical settings and using the International Classification of Functioning, Disability and Health (ICF).Data extraction and synthesis Two authors independently screened articles and assessed methodological quality. Risk of bias was assessed using the Critical Appraisal Skills Programme tool for qualitative and for cohort studies, the Mixed Methods Appraisal Tool for mixed-methods studies and the JBI Critical Appraisal Checklist for analytical cross-sectional studies.Results From 3820 records screened, 9 observational studies met inclusion criteria. Key factors influencing EHR adoption included organisational readiness, perceived usefulness, managerial support and training availability. Implementation patterns clustered into three domains: recorded content, ICF framework integration and record quality. Reported outcomes focused on care quality metrics and evidence of clinical effectiveness.Conclusions Persistent challenges in physiotherapy EHR use were identified, notably in data quality, completeness and alignment with the ICF framework. Improving EHR practices is crucial to improve clinical assessment and support digital health integration. However, limited evidence and methodological heterogeneity remain key limitations.PROSPERO registration number CRD42023420267.